2018
DOI: 10.19175/recom.v8i0.2327
|View full text |Cite
|
Sign up to set email alerts
|

Principais complica��es apresentadas durante a hemodi�lise em pacientes cr�ticos e propostas de interven��es de enfermagem

Abstract: Objetivos: Identificar complica��es apresentadas durante as sess�es de hemodi�lise em pacientes de uma terapia intensiva do Distrito Federal. M�todos: Estudo descritivo, quantitativo, realizado num hospital p�blico de Bras�lia, entre junho a agosto de 2015. Os dados foram coletados atrav�s de formul�rio e foram analisadas caracter�sticas como: prescri��o da hemodi�lise, sinais vitais e complica��es durante as sess�es de hemodi�lise. Resultados: Foram analisadas 31 sess�es de hemodi�lise, com dura��o de tr�s a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…It is known that, currently, hemodialysis does not only seek to reverse uremic symptoms, but also reduces the complications inherent in the procedure itself and reduces the risk of mortality. 22 It was pointed out the prevalence of hypotension as an intradialytic complication in this study, associated with the hemodynamic fragility in the patient and also the primary reflex of the large amount of fluid that is extracted from the plasma volume during a routine dialysis session; the water, which is accumulated in the interdialytic range, is extracted directly by the ultrafiltration mechanism. 23 In this study, arterial hypertension was the second most frequent complication, also reported in another study, since the kidneys stimulate the production of vasoconstrictors and vasodilators.…”
Section: Comorbiditiesmentioning
confidence: 70%
“…It is known that, currently, hemodialysis does not only seek to reverse uremic symptoms, but also reduces the complications inherent in the procedure itself and reduces the risk of mortality. 22 It was pointed out the prevalence of hypotension as an intradialytic complication in this study, associated with the hemodynamic fragility in the patient and also the primary reflex of the large amount of fluid that is extracted from the plasma volume during a routine dialysis session; the water, which is accumulated in the interdialytic range, is extracted directly by the ultrafiltration mechanism. 23 In this study, arterial hypertension was the second most frequent complication, also reported in another study, since the kidneys stimulate the production of vasoconstrictors and vasodilators.…”
Section: Comorbiditiesmentioning
confidence: 70%
“…Diante disso, é exigido que sejam planejados cuidados sistematizados para fortalecer o cuidado por parte da equipe de enfermagem envolvida na diálise. O uso de protocolos institucionais validados conduz à maior segurança nas intervenções que são realizadas (SILVA et al, 2018), constituindo uma situação que demanda educação permanente da equipe e atenção das instituições formadoras.…”
Section: Resultsunclassified
“…Os eventos: isquêmicos, infecciosos, obstrutivos, insuficiência cardiovascular, hepática e respiratória favorecem para o advento da DRC (SILVA et al, 2018). No entanto, os riscos para a DRC envolvem indivíduos com diabetes tipo 1 e 2; com: hipertensão arterial; idosos; portadores de obesidade; histórico de doenças circulatória e DRC na família; tabagismo e uso de nefrotóxicos (BRASIL, 2014).…”
Section: Doença Renal Crônica (Drc)unclassified
“…Dentre as complicações decorrentes da hemodiálise encontra-se as relacionados ao acesso vascular, principalmente na punção da veia subclávia com incidência aumentada para: pneumotórax, hemotórax, perfusão da artéria subclávia e lesão do plexo braquial, sendo o ideal na veia jugular interna direita. Além do mais, a posição inadequada do cateter pode levar à obstrução do lúmen por coágulo, interrompendo o fluxo sanguíneo com a máquina (SILVA et al, 2018).…”
Section: Hemodiáliseunclassified